Ultra-fast pencil beam scanning proton therapy for locally advanced non-small-cell lung cancers: Field delivery within a single breath-hold. (September 2022) - Maradia, Vivek; van de Water, Steven; Meer, David; Weber, Damien C.; Lomax, Antony J.; Psoroulas, Serena
Highlights: PBS proton therapy within a single breath-hold (15 sec). Hypofractionation within a single breath-hold. Treatment of moving targets. Abstract: Purpose: The use of motion mitigation techniques such as breath-hold can reduce the dosimetric uncertainty of lung cancer proton therapy. We studied the feasibility of pencil beam scanning (PBS) proton therapy field delivery within a single breath-hold at PSI's Gantry 2. Methods: In PBS proton therapy, the delivery time for a field is determined by the beam-on time and the dead time between proton spots (the time required to change the energy and/or lateral position). We studied ways to reduce beam-on and lateral scanning time, without sacrificing dosimetric plan quality, aiming at a single field delivery time of 15 seconds at maximum. We tested this approach on 10 lung cases with varying target volumes. To reduce the beam-on time, we increased the beam current at the isocenter by developing new beam optics for PSI's PROSCAN beamline and Gantry 2. To reduce the dead time between the spots, we used spot-reduced plan optimization. Results: We found that it is possible to achieve conventional fractionated (2 Gy(RBE)/fraction) and hypofractionated (6 Gy(RBE)/fraction) field delivery times within a single breath-hold (<15 sec) for a variety non-small-cell lung cancer cases. Conclusion: In summary, the combination of spot reduction and improved beam line transmission is a promising approach for the treatment of mobile tumours within clinically achievable breath-hold durations.